Integrating a Positron Emission Tomography/Computed Tomography Into the National Health System of Cyprus: Will It Return on Its Investment? - Kefallonitou, Dimitra; Polycarpou, Irene; Souliotis, Kyriakos; Giannakou, Konstantinos (Frontiers in Public Health, 2021)
Α European Union (EU) member state, Cyprus is a country with a population of approximately 850.000 citizens. According to the Cyprus Ministry of Health, since 2009, more than 3.000 new incidents with neoplasm are diagnosed every year (i.e. 3% increasing rate). Projections estimate an average annual increase of 2.2% of new incidents until 2040. However, the National Health System (NHS) of Cyprus lacks a Positron Emission Tomography/Computed Tomography (PET/CT) care framework and infrastructure. Patients can only have a PET/CT exam in the private sector, either in Cyprus or a neighbouring country (e.g. Greece or Israel). This requires the government of Cyprus to cover financial expenses related to medical treatments while the patients may also need to cover their expenses for travelling to a neighbouring country. This study presents a cost analysis to examine whether the integration of a PET/CT with, or without, an F18-FDG cyclotron unit in the NHS of Cyprus is an efficient investment that can be recovered within the unit’s service life. To perform this study, we estimated necessary resources for purchasing and operating such unit for a period of 15 years. The results of this study indicate that an investment in a PET/CT unit is not financially viable. Alternatives, such as the reimbursement of PET/CT operated by the private sector is recommended.